Comparative larval morphology in Madagascan frogs of the genus Guibemantis (Amphibia: Mantellidae) - Vejarano, Silvia; Thomas, Meike; Vences, Miguel (Zootaxa, 2006)
We describe the tadpole morphology for four species of frogs classified in the endemic Madagascan genus Guibemantis, based on larval specimens identified by DNA barcoding. The tadpoles of Guibemantis kathrinae and G. tornieri are reported for the first time. The tadpole of G. kathrinae has a heterogeneous coloration, emarginated oral disc bordered with papillae and one row of submarginal papillae. Labial tooth row formula is 6(2–6)/3(1). Number of labial teeth per millimetre is variable in each row, ranging from 36 to 64. The tadpole of G. tornieri is very similar to that of G. timidus (previously considered conspecific with G. tornieri) except for the patched coloration of G. tornieri (vs. rather uniform in G. timidus). The tadpole of G. depressiceps is characterized by having a higher number of teeth per millimetre in all tooth rows than the other species of the group. The tadpole of Guibemantis liber differs from the other species by having a lower number of upper labial tooth rows (two, three or four vs. five or more). No morphological differences were found between larvae of G. liber from two separate localities, Ranomafana and Andasibe. In general, the Guibemantis larvae examined (except G. liber) are morphologically similar to each other but several of the characters examined were highly variable within populations and species, highlighting the usefulness of molecular tools for their identification.